A Systematic Literature Review to Identify Empirical Evidence on the use of Games]Based Learning in Primary Education for Knowledge Acquisition and Content Understanding - Hainey, Thomas; Connolly, Thomas; Boyle, Elizabeth; Azadegan, Aida; Wilson, Amanda; Razak, Aisya; Gray, Grant (European conference on games based learning, 2014)
Games-based learning has developed a reputation with educationalists as it is perceived as a potentially engaging form of supplementary learning that could be utilised to enhance the educational process. Games-based learning has been utilised at all levels of education including primary, secondary and tertiary education. Despite this recognition and utilisation there is still a lack of empirical evidence to support the validity of games-based learning as an approach. This paper will present the findings of a systematic literature review performed from 2000 to 2013 specifically looking at quality empirical studies associated with the application of games-based learning in Primary Education (PE) level. The results presented in this paper are a subset of a larger study categorising studies into: behavioural change, affective and motivational outcomes, perceptual and cognitive skills, knowledge acquisition and content understanding and soft skill outcomes. This paper will specifically focus on the knowledge acquisition and content understanding category where 68 studies were identified; overall however only 29 of those studies made it over the quality assurance threshold. This paper will present a synthesis of these high quality studies associated with knowledge acquisition and content understanding. The studies showed that games-based learning has been used to teach a variety of subjects to children and young people under the age of 14 with mathematics, science, language and social studies being the most popular.